A comparison of mobile banking service quality between APP and web browser. (2018) - Tsai, Ming-Chun; Lin, Shou-Yen; Lin, Shu-Ping
This study aimed to explore the customer demands for service quality on both the application (APP) platform and web browser platform, and compare the differences of service demands among customers of different ages regarding the APP platform and web browser platform. A questionnaire survey was conducted on banking customers of the APP platform and web browser platform in Taiwan. This study utilised the moderated regression model to classify Kano two-dimensional quality. The findings showed that the Kano two-dimensional quality of mobile banking service was quite different between the APP platform and the web browser platform. The service demands among customers of different ages were also quite different regarding the APP and web browser platforms. These results suggested that the management strategies of mobile banking should be put forward according to customer demands for service quality on the different platforms.